The effect of low impact aerobic exercise on increasing physical fitness for the elderly - Cerika Rismayanthi; Muhammad Ikhwan Zein; Rizki Mulyawan; Risti Nurfadhila; Rifky Riyandi Prasetyawan; Muhammad Sigit Antoni (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aimed to investigate the effect of low-impact aerobic exercise on increasing physical fitness for the elderly. This one group of pretest-posttest quasi-experimental research recruited elderly subjects from Sumber Waras Elderly Association in Yogyakarta, Indonesia. Twenty-four elderly subjects aged 60-70 years old participated in the 16 sessions of aerobic exercise intervention. All subjects completed pre-and post-intervention physical fitness tests comprising the aerobic/cardiovascular (CV) endurance (2 minutes step test), upper body strength (arm curl test), lower body strength (chair stand test), upper body flexibility (back scratch test), core and lower body flexibility (sit and reach test) and balance (8 foot up and go test). Changes in physical fitness (post- versus pre-intervention) of the subjects were analyzed using paired T-test. The normality and homogeneity tests were performed using the Kolmogorov Smirnov and Levene’s tests, respectively. Statistical significance was set to p 0.05. This study showed that all physical fitness components, including aerobic endurance, upper and lower body strength, upper and lower body flexibility, and balance, were increased significantly in the subjects (p 0.05). The results suggest that low-impact aerobic exercise positively affects physical fitness improvement in the elderly.